Is increasing income the only reason for rural labor mobility?—A case study of Heilongjiang, China - Hao, Yanzhi; Chi, Jia; Wang, Gangyi (Frontiers in Sustainable Food Systems, 2023)
Introduction It is widely known that rural labor mobility is of the utmost importance for the livelihoods of families in rural areas of developing countries. While it increases the income and overall labor productivity of rural households, it also creates many inevitable rural recessions. Existing studies have different views on whether increasing income is the only reason for rural labor mobility. Methods This paper discusses the influencing factors of rural labor mobility and investigates research on the causes of rural labor mobility. To do so, the study analyzes micro-survey data of 47 villages in 13 cities in Heilongjiang province, China, from 2014 to 2019. Considering the basic situation of rural families and labor mobility, the actual demand for rural laborers in Heilongjiang province is also analyzed. Results The research results show that increasing income is not the only reason for the flow of rural labor, and that rural labor mobility requires more than just rising incomes. Discussion This study's main contribution is identifying that increased income does have a positive and significant impact on rural labor mobility, but seeking job opportunities, pursuing better-quality education for children, and developing prospects are significant factors in the current rural labor mobility.